Design it yourself graphic workshop : a step-by-step guide - Green, Chuck (Charles K.) (Rockport, 2011)
New in Paperback! The book non-designers can count on for creating winning designs Do you want a concise how-to book on graphic design that avoids all the theory and just gets down to the nuts and bolts of getting a project done? Then this book is for you.